ANALYSIS OF TAX POLICY AND REGULATION ON FINTECH SERVICES IN INDONESIA: IMPACT ON INNOVATION AND THE DIGITAL ECOSYSTEM - Fittry Megasari Sijabat (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The rapid development of the financial technology (fintech) industry in Indonesia has had a significant impact on the transformation of digital financial services. However, this growth has also given rise to an urgent need for balanced tax and regulatory policies to ensure innovation and the sustainability of the digital ecosystem. This study aims to analyse the influence of tax and regulatory policies on fintech service innovation and its impact on the digital ecosystem in Indonesia. The method used is a literature review with a content analysis approach to various regulatory documents, official reports, and academic literature related to fintech taxation and regulation. The results show that overly burdensome tax policies can hinder innovation, while adaptive regulations, such as the implementation of regulatory sandboxes, can promote the healthy and inclusive growth of fintech services. Therefore, a balance between fiscal and regulatory aspects and synergy among stakeholders are key to the successful development of a competitive and sustainable fintech industry in Indonesia.